Analysis of genetic variants associated with the removal of the pathological Abeta form in patients with Alzheimer's disease. (1st February 2022) - Dorszewska, Jolanta; Prendecki, Michal; Hurla, Mikolaj; Banaszek, Natalia; Szejn, Paulina; Florczak‐Wyspianska, Jolanta; Ilkowski, Jan; Kozubski, Wojciech
Abstract: Background: Alzheimer's disease (AD) is a dementia disease with a pathomechanism that is not fully understood. There are currently over 20 known genes associated with AD. These genes are involved in metabolism, the removal of abnormal products, including Aβ. Exosomes may be involved in removing abnormal proteins in AD. It is believed that the APOE, RAB11A and TSG101 genes may influence the functioning of exosomes. APOE E4 gene reduces ability to clear Aβ by affecting microglia function. TREM2, acts as a receptor for the Aβ oligomers and mediates its degradation by microglia. Both the CD33 and MS4A4A genes are also responsible for maintaining the efficiency of the immune system. So far, the correlation between these genes has not been studied in AD. The aim of the study was to analyze of genetic variants RAB11A (exon 2), TSG101 (exons 8, 9), CD33 (rs3865444), MS4A4A (rs6591561), TREM2 (rs75932628 and rs143332484) in AD patients, control subjects related to AD cases (CR), and controls subjects without family history of AD (CU). Method: The studies were conducted on 170 individuals (AD and controls). The APOE genotype was determined by real‐time PCR. The RAB11A, TSG101, CD33, MS4A4A, TREM2 genetic variants were determined by HRM and sequencing. Result: The C/T variant of the TREM2 rs143332484 was a probable risk factor for AD. People carrying the pathogenic TREM2 rs143332484‐C/T variant tended to have earlier onset of symptoms and faster progression of AD (p<0.05). Variant C/A CD33 rs3865444 was more frequent in patients with AD. The CD33 gene, a very rare polymorphism was detected: rs562148996‐C/T. The C/A + C/T CD33 gene tended to occur more frequently in controls. The presence of the CD33 rs3865444‐A/A might have indicated a protective effect in AD. The MS4A4A rs6591561‐A variant was probably associated with the progression of dementia in patients with AD. Dementia tended to develop faster in A/A homozygotes, and slower in patients with the G/G genotype. Conversely, mutations in the RAB11A and TSG101 genes did not appear to affect the onset of AD. Conclusion: Genes associated with removal of pathogenic Aβ deposits seem to be involved in the pathogenesis of AD.